Inhibition of AGEs-RAGE-PP2A Axis Alleviates Cognitive Impairment after Chronic Heart Failure: Heart failure induces cognitive impairment - Li, Shaodong; Wang, Linhai; Wang, Junyan; Liang, Birong; Gao, Wenbin; Huang, Yusheng; Deng, Bo; Liu, Qing; Zhou, Zheng; Zhang, Lu; Xian, Shaoxiang; Wang, Lingjun; et al. (Cellular and Molecular Biology, 2023)
To investigate the effect of the AGEs-RAGE-PP2A axis on cognitive impairment (CI) after chronic heart failure (CHF). Mice were divided into six groups: Sham, TAC, Sham+RAGE-/-, TAC+RAGE-/-, AG, and FTY720 group. AG mice and FTY720 mice were treated with AGEs inhibitor (aminoguanidine, AG) and PP2A activator (FTY720) respectively after TAC surgery. The cardiac function of AG and TAC+RAGE-/- mice was significantly better than that of TAC mice (P<0.05). However, the heart function of FTY720 mice were just improved a part of that. To behavioral function, the escape latency period of the TAC+RAGE-/-, AG and FTY720 mice were significantly shorter (P<0.05), and the times of platform crossings and residence time of them were significantly improved (P<0.05). HE staining and silver staining show the structure of TAC+RAGE-/-, AG and FTY720 mice were more complete. Also, in these three groups, the expression of Aβ and p-tau protein in the brain can be significantly down-regulated (P<0.05) and the PP2A protein expression level was up-regulated (P<0.05). And the expression of hippocampal Bax, Cyt-C, and Caspase-3 of that were all down-regulated (P<0.05), and Bcl-2 was up-regulated (P<0.05). Deficient of AGEs, RAGE and activating PP2A can significantly attenuate the cognitive impairment in CHF mice, and protect the brain structure. This mechanism seems via reducing the expression of Aβ, p-tau, and apoptotic protein.